Pengukuran Metrik Kompleksitas Model Proses Bisnis Sekolah - Yaqin, Muhammad Ainul; Pratama, Dicky Eka Asia; Rofi’uruttab, Mohammad; Cahya, Ilman Dwi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
School as an institution that has a primary mission to educate and develop the character of the nation through a series of learning activities. School is an organization whose success goals are largely determined by the leadership style and organizational paradigm that is shared by all school components. Schools as organizations have business processes as a collection of procedures or activities that can define business objectives or objectives, generally in the context of organizational structures that can define functional roles and relationships within the organization. The main purpose of BPMN is to provide a notation that is easy to use and can be understood by everyone involved in business, which includes business analysts who model business processes, technical developers who build systems that carry out business, and various levels of management that must be able to read and understand processes diagram quickly so that it can help in decision making. To measure the complexity of a business process, complexity metrics are measured. This study uses the Cognitve Information Complexity Measure (CICM) method. Researchers took 3 SOPs of national education standards namely SOP curriculum development resulting in a standard value of complexity 425.1496, SOP for the Learning Process produced a standard value of complexity 2091.333 and SOP for Teacher Recruitment resulted in a standard value of complexity of 1145.49.